Application of the AP4M Model in Reading the Understanding of Genre Narrative Text through E-Learning - Gusnetti Gusnetti; Agustina Agustina; Ermanto Ermanto; M. Zaim (INTERNATIONAL JOURNAL OF LANGUAGE PEDAGOGY, 2021)
This research was motivated by observations and interviews of learning tools for reading skills lectures in the Indonesian Language and Literature study program, Bung Hatta University. It is known that reading courses are generally given in the form of minimal reading theory and practice. As a result, students have difficulty understanding the reading text because students do not know the genre of the text being read. To solve this problem, one of the alternatives proposed is to apply the AP4M Model in Reading Comprehension of Narrative Text Genres through E-Learning. The research objective was to describe students' reading comprehension skills using the AP4M model. This research uses qualitative and quantitative methods. The research subjects were students of the Indonesian Language and Literature Study Program, Bung Hatta University, Padang, class 2019/2020. The results showed that the students' ability to determine themes and messages was 8.90; determine the type of narrative text and its description 8.90; determine the structure of the narrative text genre 9.80; determine the character of the character 7.8. The results of the research on the application of the AP4M Model in reading comprehension of the narrative text genre of students were 8.6 with the very good category.